2018
DOI: 10.1111/hae.13473
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding‐related hospitalization in patients with von Willebrand disease and the impact of prophylaxis: Results from national registers in Sweden compared with normal controls and participants in the von Willebrand Disease Prophylaxis Network

Abstract: Our study indicates that subjects with VWD have a considerably higher consumption of healthcare resources compared to controls and that initiation of prophylaxis may reduce the number of hospitalizations due to bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 9 publications
2
54
0
Order By: Relevance
“…Gastrointestinal (GI) bleeding is the most frequent cause of hospitalization in von Willebrand disease (VWD). 1,2 VWD patients often present with recurrent overt or occult GI bleeding from an unidentified source on conventional endoscopy. 3 This clinical picture is assumed to be related to an increased incidence of GI angiodysplasia in VWD.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GI) bleeding is the most frequent cause of hospitalization in von Willebrand disease (VWD). 1,2 VWD patients often present with recurrent overt or occult GI bleeding from an unidentified source on conventional endoscopy. 3 This clinical picture is assumed to be related to an increased incidence of GI angiodysplasia in VWD.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies have reported estimates of VWD prevalence in the general population with estimates ranging between 0.1% and 1%, [8][9][10] and to our knowledge, no previous study has presented results for overall or trends in incidence of VWD at a population level. Thus, while VWD might be the most common bleeding disorder, we lack information about the epidemiology of VWD and the potential unmet treatment needs in this patient population.…”
mentioning
confidence: 83%
“…4 Patients with VWD may experience lower quality of life 6,7 and have more hospital contacts and longer hospital stays compared to the general population. 8 It is therefore important to identify and treat symptomatic VWD early to alleviate the psychological and physiological distress of the individual and the burden on the health care system caused by undiagnosed patients.…”
mentioning
confidence: 99%
“…Long-term prophylaxis in VWD is being used increasingly common 53 to prevent secondary complications, reduce hospitalization, and improve quality of life. 34,54,55 Due to the late onset of clinically relevant bleeding, prophylaxis in patients with VWD is usually secondary prophylaxis, 35,53 which is started in early adulthood. 54 Bleeding scores can help to assess the severity of bleeding tendency.…”
Section: Vwd and Prophylaxismentioning
confidence: 99%
“…34,54,55 Due to the late onset of clinically relevant bleeding, prophylaxis in patients with VWD is usually secondary prophylaxis, 35,53 which is started in early adulthood. 54 Bleeding scores can help to assess the severity of bleeding tendency. 23,56 Indications for prophylaxis may be severe VWD with recurrent forms of GI bleeding, joint bleeding, severe nose bleeding, menorrhagia and in cases which could not adequately controlled with other therapeutic options.…”
Section: Vwd and Prophylaxismentioning
confidence: 99%